In Response to: Determinants of Olympic fencing performance and implications for strength and conditioning training - Bottoms, L. M.; Wylde, M. J. (The Journal of Strength and Conditioning Research, 2017)
Thank you for raising these issues and the debate this has generated. Below, we have responded to all your points, where our aim is to show that our contention is not with the need to develop an aerobic base, but rather the extent to which it should be developed and the methods used in achieving this. Also, while we recognize there are 3 swords, we will outline an argument that the strength and condition- ing (S&C) programming for these does not differ. Naturally, these are our inferences, so at times it is not about disproving your argument, but rather presenting a logical alternative.